2022
DOI: 10.1371/journal.pone.0247629
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-connectivity between the left motor cortex and prefrontal cortex is associated with the severity of dysfunction of the descending pain modulatory system in fibromyalgia

Abstract: Introduction The association between descending pain modulatory system (DPMS) dysfunction and fibromyalgia has been previously described, but more studies are required on its relationship with aberrant functional connectivity (FC) between the motor and prefrontal cortices. Objectives The objective of this cross-sectional observational study was to compare the intra- and interhemispheric FC between the bilateral motor and prefrontal cortices in women with fibromyalgia, comparing responders and nonresponders t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 80 publications
0
4
1
Order By: Relevance
“…Consequently, the decreased connectivity for prolonged pain stimulation periods may not generalise to other experimental pain conditions. Indeed, unlike our findings with brain-wide disconnection in response to painful stimulation, other studies that investigate pain-related connectivity in response to brief pain have reported increased connectivity during pain perception 38 , 39 .…”
Section: Discussioncontrasting
confidence: 99%
“…Consequently, the decreased connectivity for prolonged pain stimulation periods may not generalise to other experimental pain conditions. Indeed, unlike our findings with brain-wide disconnection in response to painful stimulation, other studies that investigate pain-related connectivity in response to brief pain have reported increased connectivity during pain perception 38 , 39 .…”
Section: Discussioncontrasting
confidence: 99%
“…The SI is responsible for encoding sensory aspects of pain, whereas the ACC is involved in affective processing. According to an earlier study, when patients with central sensitization are exposed to sensory stimuli, there is more neuronal activity in areas that process sensory information ( de Oliveira Franco et al, 2022b ). Significant structural, chemical, and functional changes have also been observed in pain-related brain areas, such as the cingulate and somatosensory cortices ( Nir et al, 2008 ; Harte et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Discriminatory analysis indicated a significant difference in group interconnectivity patterns [9]. Even though there is evidence that dysfunctional processing in FM is caused by dysfunctional connectivity and dysfunction of the DPMS [7,10], there is not much evidence about how treatment affects these neural markers. Thus, it is crucial to investigate the effect of treatments on these neural markers associated with the severity of pain symptoms, which can help develop effective treatments for pain management and personalized treatment.…”
Section: Introductionmentioning
confidence: 97%
“…FC is the degree to which activity between a pair of brain regions covaries or correlates over time. In FM, the descending pain modulatory system (DPMS) does not work as well when there is more functional connectivity (FC) between pain processing areas like the left motor cortex (MC) and the left prefrontal cortex (PFC), as well as between the left MC and the right PFC [7]. Another study in FM found an increased delta value of FC in response to acute pain between the PFC and MC in genotypes BDNF Val/Met compared to Val/Val [8].…”
Section: Introductionmentioning
confidence: 99%